Digital Pedagogy in Early Childhood Education: Exploring Teacher and Parent Knowledge, Expectations, and Problems - Jumiatmoko, Jumiatmoko; Rasmani, Upik Elok Endang; Winarji, Bambang; Zuhro, Nurul Shofiatin; Fitrianingtyas, Anjar; Nurjanah, Novita Eka (Jurnal Pendidikan Progresif, 2025)
Digital Pedagogy in Early Childhood Education: Exploring Teacher and Parent knowledge, expectations, and problems. Objectives: This study identifies teachers’ and parents’ knowledge, expectations, and problems related to the implementation of digital pedagogy in ECE. Methods: A mixed-methods approach was used to present quantitative and qualitative data in an explanatory design. The main respondents in this study were teachers. Data related to parents were obtained from teachers’ answers, which were also filled in the questionnaire. There were 196 respondents of ECE teachers from 5 provinces in Indonesia. Quantitative data analysis with SPSS version 25 software was used to examine perceptions, abilities, and correlations between both. Qualitative data using thematic analysis to identify expectations and problems related to digital pedagogy implementation. Findings: Teachers have positive perceptions but low digital pedagogy implementation capabilities. The quantitative data findings regarding low teacher capabilities (average score <3.0) are confirmed by the qualitative data findings regarding challenges to the implementation of digital pedagogy in the teacher training needs and infrastructure limitations as the most significant potential factors. Several expectations were found related to improving teacher competency and technical understanding of the use of digital devices. Other challenges to implementing digital pedagogy include a lack of parental support and several issues related to children’s physical, social, and psychological health. Conclusion: Teachers’ knowledge of digital pedagogy confirms paradoxical interactions. Positive perceptions are not yet in line with teachers’ abilities in implementing digital pedagogy. Play-based Digital Pedagogy (PBDP) and Domestication theory have excellent potential to be considered in this context. This theory is able to provide clear guidelines to improve teachers’ abilities in implementing digital pedagogy ideally. Furthermore, the phases recommended by domestication theory are expected to be able to meet expectations and resolve obstacles to the implementation of digital pedagogy. Keywords: pedagogy, digital, early childhood, teacher competency, domestication theory.